Pengaruh Kegiatan Ekstrakurikuler Terhadap Karakter Peserta Didik Di Sekolah Dasar - Hana Nurur Rohmah; Nabella Yaniariza Putri; Septi Yunita; Yunita Yasmin; Agus Mulyana (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
This study aims to determine the effect of extracurricular activities carried out in elementary schools on the formation of students' character. The type of research used in this research is library research from research that has been done before. The method used in this study is using qualitative methods. Data collection in this study was carried out by means of literature studies from journals, books, and other sources that have been recognized for their accuracy. The results of the analysis from this study indicate that there is a visible influence from extracurricular activities on the character of students in elementary schools. With the extracurricular activities carried out, students can develop their character and interests and talents.